2007
DOI: 10.1152/ajpgi.00464.2006
|View full text |Cite
|
Sign up to set email alerts
|

Role of calcitonin receptor-like receptor in colonic motility and inflammation

Abstract: A. Role of calcitonin receptor-like receptor in colonic motility and inflammation. Am J Physiol Gastrointest Liver Physiol 293: G36-G44, 2007. First published March 15, 2007 doi:10.1152/ajpgi.00464.2006.-Calcitonin gene-related peptide (CGRP) mediates neurogenic inflammation and modulates intestinal motility. The CGRP receptor is a heterodimer of calcitonin receptor-like receptor (CLR) and receptor-associated modifying protein 1. We used RNA interference to elucidate the specific role of CLR in colonic motilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 33 publications
1
36
0
Order By: Relevance
“…As CGRP has diverse roles in different tissues (23)(24)(25), a targeted local delivery of dsRNA for CLR or CGRP is preferable. In agreement with previous findings, our dsRNA was not proinflammatory, because it did not alter weight gain or basal levels of intestinal secretion or cytokines and MPO activity (20,26) and, importantly, CLR dsRNA specifically ameliorated TxA-induced ileitis. Because local injection of CLR dsRNA universally improved all end points of TxA-induced ileitis examined, our current findings suggest efficacy for encapsulated or luminal delivery of dsRNA to alter local inflammation in the gastrointestinal tract.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…As CGRP has diverse roles in different tissues (23)(24)(25), a targeted local delivery of dsRNA for CLR or CGRP is preferable. In agreement with previous findings, our dsRNA was not proinflammatory, because it did not alter weight gain or basal levels of intestinal secretion or cytokines and MPO activity (20,26) and, importantly, CLR dsRNA specifically ameliorated TxA-induced ileitis. Because local injection of CLR dsRNA universally improved all end points of TxA-induced ileitis examined, our current findings suggest efficacy for encapsulated or luminal delivery of dsRNA to alter local inflammation in the gastrointestinal tract.…”
Section: Discussionsupporting
confidence: 93%
“…We previously showed that CLR is required for functional responses to CGRP (20). CLR and RAMP1 comprise the CGRP receptor (6), and are colocalized throughout the gastrointestinal tract in nerve fibers and soma that may participate in TxA enteritis (7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pharmacological blockage of the SP receptor neurokinin (NK)1 was benefi cial in TNBS and DSS colitis (57,58) . Recent studies on SP, CGRP and double knockout mice confi rmed the pro-infl ammatory effects of SP in experimental colitis and demonstrated the protective effects of CGRP (56,59) , which had been suggested previously (60,61) . Several in vitro studies showed that the effects of SP and CGRP on the immune system are very complex and are more extensive than those of classical neurogenic infl ammation, which comprises vasodilatation and plasma extravasation.…”
Section: Colitis -A Disease Of the Sensory Nervous System ?mentioning
confidence: 64%